MiR-223 promotes pyroptosis of enteritis cells through activating NF-κB signalling pathway by targeting SNIP1 in inflammatory bowel disease - Li-Ze Zhang; Hui Xue; Cui-Xia Qiao; Wen-Li You; Ai-Ting Di; Gang Zhao (Taylor & Francis Group, 2021)
Inflammatory bowel disease (IBD) is a common inflammation-related intestinal disease. Studies have shown that excessive pyroptosis of intestinal cells is involved in the development of IBD. However, the regulatory mechanism of pyroptosis in IBD remains unclear. Here, our study purposed to clarify the underlying regulatory mechanism of miR-223 to promote pyroptosis in IBD. MiR-223 and Smad Nuclear Interacting Protein 1 (SNIP1) expression in colon tissues collected from IBD patients and healthy volunteers were evaluated using qRT-PCR. Cell viability and pyroptosis were evaluated by CCK8 and flow cytometry assay, respectively. Pyroptosis-related proteins and nuclear factor κB (NF-κB) signals were determined by WB. Dual-luciferase reporter gene assay was employed to investigate the binding relationship between miR-223 and SNIP1. MiR-223 was significantly upregulated in IBD colon tissues and cell models, while SNIP1 was significantly decreased. Silence of miR-223 markedly enhanced cell viability and inhibited pyroptosis in the IBD cell model. MiR-223 could bind to 3'-UTR of SNIP1 and SNIP1 could activate NF-κB signalling pathway. Further rescued experiment found that knockdown of SNIP1 dramatically abolished the bio-effects mediated by miR-223 silence on the cell viability and pyroptosis of the IBD cell model. Likewise, the inactivation of NF-κB signalling markedly weakened the regulatory roles of SNIP1 downregulation in the IBD cell model. Besides, inhibition of NF-κB signalling attenuated the pyroptosis-promoting effect of overexpressing miR-223. Our data suggested that miR-223 activated the NF-κB pathway via targeting SNIP1, thus promoting the process of cell pyroptosis, and ultimately participating in the pathogenesis of IBD.